Consumer Protection Against the Circulation of Illegal Skincare Products on E-Commerce Platforms in Makassar - Alifia Rosa Anggreani; Ahmad Syahird; Irwan; Dinar Alqadri (Realism: Law Review, 2026)
The rapid growth of e-commerce has reshaped the distribution of skincare products in Indonesia while simultaneously increasing the circulation of illegal products through digital platforms. Many are sold without BPOM authorization, contain harmful substances, or provide misleading information, posing risks to consumer health and safety. This study analyzes the effectiveness of consumer protection against illegal skincare products on e-commerce platforms in Makassar and examines the legal responsibilities of platforms in preventing such circulation. Using normative legal research with statutory, conceptual, and analytical approaches, data were collected through library research and analyzed qualitatively with a descriptive-analytical method. Findings show consumer protection remains ineffective due to weak digital supervision, open marketplace systems, information asymmetry, and limited public legal awareness. Although platforms apply seller verification, product monitoring, takedown mechanisms, account suspension, and complaint services, these measures are largely reactive. Doctrinally, the study argues that the legal framework has not clearly imposed a preventive duty of care on e-commerce platforms as Electronic System Providers. Platform responsibility should extend to proactive legality verification and integrated supervision with BPOM. Strengthening regulatory coordination, digital monitoring, and platform accountability is essential to ensure legal certainty, justice, and effective consumer protection in Indonesia’s digital marketplace.